CSF-Derived CD4+ T-Cell Diversity Is Reduced in Patients With Alzheimer Clinical Syndrome. Issue 1 (January 2022) - Joshi, Chaitanya; Sivaprakasam, Karthigayini; Christley, Scott; Ireland, Sara; Rivas, Jacqueline; Zhang, Wei; Sader, Danielle; Logan, Rebecca; Lambracht-Washington, Doris; Rosenberg, Roger; Cullum, Munro; Hitt, Brian; et al.
Abstract : Background and Objectives: Patients with Alzheimer dementia display evidence of amyloid-related neurodegeneration. Our focus was to determine whether such patients also display evidence of a disease-targeting adaptive immune response mediated by CD4 + T cells. To test this hypothesis, we evaluated the CSF immune profiles of patients with Alzheimer clinical syndrome (ACS), who display clinically defined dementia. Methods: Innate and adaptive immune profiles of patients with ACS were measured using multicolor flow cytometry. CSF-derived CD4 + and CD8 + T-cell receptor repertoire genetics were measured using next-generation sequencing. Brain-specific autoantibody signatures of CSF-derived antibody pools were measured using array technology or ELISA. CSF from similar-age healthy controls (HCs) was used as a comparator cohort. Results: Innate cells were expanded in the CSF of patients with ACS in comparison to HCs, and innate cell expansion increased with age in the patients with ACS, but not HCs. Despite innate cell expansion in the CSF, the frequency of total CD4 + T cells reduced with age in the patients with ACS. T-cell receptor repertoire genetics indicated that T-cell clonal expansion is enhanced, and diversity is reduced in the patients with ACS compared with similar-age HCs. Discussion: Examination of CSF indicates that CD4 + T cell–mediated adaptive immune responses are altered in patients with ACS. Understanding the underlying mechanisms affecting adaptive immunity will help move us toward the goal of slowing cognitive decline.